High occurrence of giardiasis in children living on a 'landless farm workers' settlement in Araras, São Paulo, Brazil Alta ocorrência de giardíase em crianças do Assentamento Sem Terra, Araras, São Paulo, Brasil - Oswaldo Aparecido de Lima Junior; Juliana Kaiser; Rosana Catisti (Universidade de São Paulo (USP), 2013)
Enteric parasitosis remains an important public health problem in many areas around the world including in Brazil, and it is frequently associated with poverty and lack of sanitation facilities. Research carried out over the course of a year revealed that 96.6% (28/29) of children randomly selected from a 'landless farm workers' settlement in Araras, São Paulo, aged 4 - 15 years, presented Giardia intestinalis cysts. After referral to the neighborhood Health Office, all the children received tinidazole, given as a single dose of 50 mg/kg and 12 months later, new fecal samples were collected and analyzed. Despite the low adherence to the study, a high percentage (64.3% - 9/14) of the children remained positive for the parasite. This study showed a high positivity of giardiasis in child residents of the settlement, even after treatment; adults were not sensitized to the study and did not collected and/or deliver children fecal samples. The precarious living conditions are consistent with a high susceptibility to parasitic diseases, suggesting that the treatment of the infected individuals without identifying and eradicating the means of contamination is simply a palliative measure. Enteroparasitoses continuam a ser um importante problema de saúde pública em muitas áreas ao redor do mundo, bem como no Brasil, e está frequentemente associada com a pobreza e à falta de saneamento básico. Pesquisa realizada em um ano revelou que 96,6% (28/29) das crianças com idades entre quatro e 15 anos, recrutadas aleatoriamente no Assentamento Sem Terra em Araras, São Paulo, apresentaram cistos de Giardia intestinalis. Após o encaminhamento ao Posto de Saúde do bairro, todos receberam tinidazol, dose única de 50 mg/kg. Após 12 meses, novas amostras de fezes foram coletadas e analisadas. Apesar da baixa adesão ao estudo, um percentual elevado (64,3% - 9/14) de crianças permaneceu positivo para o protozoário. Este estudo mostrou alta positividade de giardíase nas crianças moradoras do assentamento, mesmo após o tratamento; ...